The Effects of Using Seaweed (E. Cottonii) on Physical Quality and Organoleptic of Chicken Nuggets (Faculty of Animal Science Universitas Brawijaya, 2008)
This research was experimental method with Completely Random Design. Seaweed used to chicken nuggets in the vary concentration, namely: 0% (F0), 10% (F1), 20% (F2), 30% (F3), 40% (F4). The observed variables were texture, water holding capacity (WHC), pH, and organoleptic quality of chicken nuggets. Collected data were analyzed using analisys variation method and followed by Duncan analysis if the result on the previous analysis showed significant difference. The result showed that chicken nuggets using seaweed gave highly significant effect (P<0.01) on texture, WHC, pH, and organoleptic quality. The best result was chicken nuggets made with used of seaweed 10%; 7.97 N of texture; 4.50% of WHC; 6.16 of pH; 6.98 of texture organoleptic score; and 6.26 of taste organoleptic score. The conclusion of this research was the using of seaweed to chicken nuggets gave a significant effect on texture, WHC, pH, and organoleptic quality. Based on the result, it suggested that using 10% of seaweed to make chicken nugeets. Keyword : water holding capacity, chicken nuggets, seaweed